Income Poverty, Subjective Poverty and Financial Stress - Marks, G (My University, 2007)
This paper focuses on financial disadvantage among Australians using data from the first two waves (2001 and 2002) of the Household, Income and Labour Dynamics in Australia (HILDA) survey.
Department of Families, Community Services and Indigenous Affairs, Social Policy Research Paper
Keywords: Stress; Finance -- Poverty and disadvantage; Stress -- Financial stress; Finance; Income, wealth and finances; Income, wealth and finances